2010
DOI: 10.1007/s10286-010-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function, gastroesophageal reflux in apparent life threatening event

Abstract: Infants with history of IALTE and GER have a significant abnormality in their autonomic control that is marked in the coupled events of apnea and GER. This finding is possibly related to medullary autonomic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This change was mainly due to a decrease in parasympathetic activity (as evidenced by the decrease in SDSD, RMSSD, HF and HF nu ). The present results support and extend the Tirosh et al's hypothesis [8] whereby autonomic alterations are associated with GER. The latter authors have shown that infants with a history of idiopathic, apparently life-threatening events display a significant HRV increase in the period preceding obstructive apnea.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This change was mainly due to a decrease in parasympathetic activity (as evidenced by the decrease in SDSD, RMSSD, HF and HF nu ). The present results support and extend the Tirosh et al's hypothesis [8] whereby autonomic alterations are associated with GER. The latter authors have shown that infants with a history of idiopathic, apparently life-threatening events display a significant HRV increase in the period preceding obstructive apnea.…”
Section: Discussionsupporting
confidence: 92%
“…It has further been hypothesized that disturbances in ANS activity could impair contraction of the lower esophageal sphincter (which normally acts as a reflux barrier) and may be involved in transient lower esophageal sphincter relaxation (and therefore also GER) [6,7]. Lastly, it has been suggested that ANS changes have a role in GER in neonates [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The adaptation to extra-uterine life is a slow and difficult process for these babies because of their prematurity. At this critical period, hypothermia, apnoea, respiratory distress, and cardiac instabilities such as bradycardia and hypotension are common features in these newborn babies (Bhatt et al, 2010;Di Fiore et al,2001;Dransfield et al, 1983;Tirosh et al, 2010;Trevisanuto et al, 2005;Upton, et al, 1992), and the resulting hypoxia may lead to brain damage and cardiac arrest if the medical support of a special incubator equipped with a ventilator and systemic monitoring is not provided a as a "primary life support system". Therefore, the continuous monitoring of heartbeat, respiration, oxygen saturation, blood pressure and temperature has been integrated into the neonatal intensive care unit (NICU) as a mandatory tool to support the fragile clinical conditions of these infants.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies were conducted in Israel, by Ari, Tirosh, Weiss, Tirosh and Goldhammer concluding to excellent prognosis among BRUE and ALTE patients and a low-yield of performed tests, with a raised possibility of an abnormality in the autonomic function related to apnea and Gastro-Esophageal Reflux (GER). 11,[17][18][19][20] Similarly, two studies underwent in Iran by Aminiahidashti and Kadivar found, respectively, a predominance of gastric etiologies and an increased incidence of 11‰ with 18 patients admitted for ALTE. 21,22 The goal of this study was to retrieve the epidemiologic characteristics of infants admitted for BRUE in Lebanon, as well as the final diagnosis and the therapeutic management.…”
mentioning
confidence: 99%